Proceedings of the 2nd Annual Conference on Social Science and Humanities (ANCOSH 2020) 2021
DOI: 10.2991/assehr.k.210413.022
|View full text |Cite
|
Sign up to set email alerts
|

Read, Encode, Annotate and Ponder (REAP) on Reading Comprehension

Abstract: The main purpose of this study was to find out the effect of Read, Encode, Annotate and Ponder (REAP) strategy towards the students' reading comprehension. It helps students comprehend the text by connecting a text with their own words to enable them to communicate their understanding of the text. This research was quasi experimental research, the subjects were 51 students, divided into 22 students of control group and 29 students of experimental group was consisting. The data was analyzed by using independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Seeing from the results of student research confirms that students are quite responsive to a change in the learning process given to them (Cantrell & Hughes, 2008;Churiyah et al, 2020). The previous research showed that The Use of Reading, Encoding, Annotating, and Pondering (REAP) strategy to improve student's' reading comprehension (Ahmad, 2019;Sholeh & Osu, 2021;Susanto, n.d.).…”
Section: Discussionmentioning
confidence: 78%
“…Seeing from the results of student research confirms that students are quite responsive to a change in the learning process given to them (Cantrell & Hughes, 2008;Churiyah et al, 2020). The previous research showed that The Use of Reading, Encoding, Annotating, and Pondering (REAP) strategy to improve student's' reading comprehension (Ahmad, 2019;Sholeh & Osu, 2021;Susanto, n.d.).…”
Section: Discussionmentioning
confidence: 78%